Grão de soja moído e níveis de amido na terminação de tourinhos Nelore confinados - Rossi, Luis Gustavo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The aim of this study was to evaluate the effect of inclusion of ground soybean with high or low level of starch in the intake, digestibility, performance, enteric methane emissions and meat quality from young bulls Nellore finished in feedlot (n = 28, initial weight = 395 + 32 kg, age = 20 + 3 months). The diets consisted of starch level, high starch (AA) or low starch (BA), with soybean (CGS) or without soybean (SGS). The roughage used was corn silage and forage: concentrate ratio in the experimental diets was 40:60. The animals were distributed in a completely randomized design in a 2x2 factorial (AA or BA; CGS or SGS), totaling four treatments with seven replicates. Data were analyzed and subjected to analysis of variance with comparison of means by Tukey test at 5% probability. After 140 days of feeding the animals were slaughtered in commercial abattoir averaging 590 ± 34 kg. Animals receiving CGS had a mean reduction of 11% of intake of dry matter, organic matter, crude protein and total digestible nutrients (P<0.05). There was a significant interaction between starch and soybean on fiber intake neutral detergent (P=0.0191), with the lowest intake for animals that received AA CGS. The addition of CGS decrease by 3% the apparent digestibility of dry matter (P=0.0282) and 2.8% of organic matter (P=0.0348). There was a significant interaction between starch and soybean on the apparent digestibility of ether extract (P=0.0245) and neutral detergent fiber (P=0.0497), with the decrease ether extract digestibility (75.05%) and neutral detergent fiber (43.19%) in AA CGS. Animals receiving CGS had an increase in feed efficiency by 17% (P=0.0076). There were no significant (P>0.05) treatments in average daily gain (average 1.38 kg), carcass yield (58.42%), gain in carcass (1.04 kg / day), area rib eye (85.60 cm2) and fat thickness (6.46 mm). Animals receiving CGS had 28% reduction of the emission of enteric methane g.dia-1 (P<0.0001). There ...

Objetivou-se avaliar o efeito da inclusão de grão de soja moído com alto ou baixo nível de amido no consumo, digestibilidade, desempenho, emissão de metano entérico, características de carcaça e qualidade da carne na terminação de tourinhos Nelore confinados (n=28, peso inicial = 395+32 kg, idade = 20+3 meses). As dietas consistiam de nível de amido, alto amido (AA) ou baixo amido (BA) com grão de soja (CGS) ou sem grão de soja (SGS). O volumoso utilizado foi a silagem de milho e a relação volumoso:concentrado nas dietas experimentais foi de 40:60. Os animais foram distribuídos em um delineamento inteiramente casualizado, num esquema fatorial 2x2 (AA ou BA; CGS ou SGS), totalizando quatro tratamentos com sete repetições por tratamento. Os dados foram analisados e submetidos à análise de variância com comparação de médias pelo teste de Tukey a 5% de probabilidade. Após 140 dias de alimentação os animais foram abatidos em frigorífico comercial com média de 590±34 kg. Os animais que receberam CGS tiveram uma redução média de 11% do consumo de matéria seca, matéria orgânica, proteína bruta e nutrientes digestíveis totais (P<0,05). Houve interação significativa entre amido e grão de soja sobre o consumo de fibra em detergente neutro (P=0,0191), sendo o menor consumo para os animais que receberam AA CGS. A adição de CGS causou efeito na digestibilidade, reduzindo em 3% a digestibilidade aparente da matéria seca (P=0,0282) e em 2,8% da matéria orgânica (P=0,0348). Ocorreu interação significativa entre amido e grão de soja sobre a digestibilidade aparente do extrato etéreo (P=0,0245) e da fibra em detergente neutro (P=0,0497), sendo a menor digestibilidade de extrato etéreo (75,0%) e fibra detergente neutro (43,1%) para AA CGS. Os animais que receberam CGS tiveram um aumento na eficiência alimentar em 17% (P=0,0076). Não houve efeitos significativos (P>0,05) dos tratamentos no ganho médio...
Keywords: Carne - Qualidade; Metano; Bovino de corte - Nutrição; Desempenho; Amido; Meat Quality